Professional Ethics and Policy Issues @ e-book / Dr. Mohamad Firdaus Ahmad ... [et al.]. - Ahmad, Mohamad Firdaus; Safwan, Nur Syazwani Zulaikha; Muhammad Rafiai, Nurul Ain; Mohamad Faisal, Nurin Amanda Amani; Mohamad Faisal, Nurin Emelda Amani; Davincy Saha, Dyvylyn Saha; Abdul Halim, Muhammad Irfan; Mohd Saat, Muhammad Akif; Meor Ab. Rahim, Mai Dhaniah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Professional Ethics and Policy Issues is the first e-book provided general knowledge related to sports industry in Malaysia with theory and International perspective. This e-book is essential reading for any student or practitioner studying or working in sports policy today. The intersection of sports with others area of governance offering a unique and comprehensive details of how sports is effected by a range of governments policy in orders to facilitate a broad understanding of sports and policy in a global context. Contemporary controversial sports issues include ergogenic aids, gambling, violence and intimidation allow the challenges facing sports ethics. A proper foundation of professional ethics needed to meet a standard of value to which all goals and action can be reach by understanding the context of this e-book.